Cultural and Symbolic Significance of Fashion Consciousness of the Yoruba Art-Headdresses - Olaleye, Samuel Kayode; Adekoya, Julius Sunday; Awosola, Taiwo Fatosin (Utan Kayu Publishing, 2025)
This paper delves into the hidden cultural and symbolic significance of Yoruba traditional headdresses, exploring their multifaceted roles within spirituality, social identity, and everyday life. Headdresses such as gele and fila are not only symbols of status, but also spiritual tools that connect the wearer to the divine and their ancestral heritage. Specific headdresses are associated with different Ori?a and carry unique meanings particularly in the areas for healing, protection, and spiritual alignment. In addition to their spiritual, cultural and symbolic significance, headdresses play a key role in Yorùbá fashion, often signifying wealth, social rank, and personal identity. Beyond aesthetics, Yoruba headdresses are also embedded in herbalism and traditional medicine, where certain caps are believed to possess healing powers. These headdresses are used in rituals to cure ailments, aids childbirth, and enhance well-being of the wearer. Unfortunately, in this contemporary period, most of these values are no longer in existence due to cultural devaluation courtesy of foreign religion, western education and embrace of foreign culture to the detriment of African/Yoruba culture. This paper therefore, explores the dynamic nature of Yorùbá headdresses, emphasizing their role in preserving cultural identity and spiritual practices. The study was carried out by conducting interview among ten Babalawo-Ifa priests, fifteen youths and fifteen elderly men and women and their views content analysed. The study recommends that the youths should be more interested in the promotion of their culture by blending it with the new found culture of the foreigners.